Mystiek van kleur. - Coessens, Piet; Tanghe, Paul (Machelen-aan-de-Leie : Roger Raveelmuseum Machelen-Zulte, 2006)
Albers, Josef ; Angeli, Marc ; Clarysse, Clark ; Cortier, Amédée ; Drieghe, Noel ; Geys, Jef ; Heyvaert, René ; De Keyser, Raoul ; Mees, Guy ; Raveel, Roger ; Rietveld, Gerrit ; Van Snick, Philippe ; Vermeersch, Pieter ; Welling, James ; Wéry, Marthe
Nederlands
Mystiek van kleur, Roger Raveelmuseum Machelen-Zulte, 26 maart - 4 juni 2006
boek